Avaliações morfofisiológicas de Ipomoea batatas L.em função da concentração de ferro - Adamski, Janete Mariza (2011)
Iron is an essential element for growth and development of plants and is involved in essential metabolic processes such as photosynthesis and respiration. However, homeostasis of this metal is essential, both excess and deficiency are harmful. One of the characteristic symptoms of deficiency is chlorosis, caused by the decrease in chlorophyll biosynthesis. On the other hand, the free iron in excess can cause oxidative stress. Study of the effects of different concentrations of iron in morphological, physiological or biochemical parameters are essential to a better understanding of this nutrient homeostasis in plants. In the present work, plants of sweet potato were submitted under hydroponics system, to different concentrations of ferric-EDTA in nutrient solution: 0.45; 0.9; 4.5 and 9.0 mmol dm-3. Photosynthetic and growth characteristics, nutrient absorption, antioxidant enzymes, stomatal density and diameter, ultra structure of root and leaves cells and histochemical iron in the leaves were evaluated. The toxicity of iron in excess (9.0 mmol dm-3) led to the appearance of brown spots on leaves, often forming necroses, with significant reductions in growth. In these plants, the activity of superoxide dismutase and ascorbate peroxidase increased. Also, the absorption of other micronutrients was affected mainly of the manganese. The iron content in the shoot increased, also qualitatively confirmed by the histochemical test. The light reactions of photosynthesis were not affected, but there was a decrease in stomatal density and net assimilation rate. The ultra structure of root cells reveals the damage of mitochondria in treatments with high concentrations of iron. However, in these plants, the ultra structure of chloroplasts is not affected.